Musyawarah Rencana Pembangunan Desa Formalistik di Desa Guwosari dan Sendangsari Kecamatan Pajangan Kabupaten Bantul - Triyanto Purnomo Raharjo; Sri Suminar; Safitri Endah Winarti; Hari Saptaningtyas (Jurnal Masyarakat dan Desa, 2021)
This research examines the implementation of the Musrenbangdes, which in many practices is only formalistic and its contributing factors. The village deliberations should not have been separated from the process of preparing a development plan in the village, so that it must involve the community in its preparation so that it is not formalistic. This type of research is descriptive. This research has its starting point on the research question of how the implementation of Musrenbangdes in Guwosari and Sendangsari villages, formalistic or not formalistic and what are the factors causing it? Qualitative analysis technique. The results showed that procedurally the Musrenbangdes in Guwosari and Sendangsari villages began with the hamlet and groups in the village (farmers, PKK, diffable and so on). Therefore, it is procedurally not formalistic. However, substantively the Musrenbangdes in the two villages run formally, because when the Musrenbangdes was held there were several community members who did not understand the material being discussed and were less active in participating in the discussion at the Murenbangdes.